Serum cytokine profiles in patients with pancreatic cancer and chronic pancreatitis - Lanki Mira; Mustonen Harri; Salmi Marko; Jalkanen Sirpa; Haglund Caj; Seppänen Hanna (Elsevier B.V., 2025)
Background: Chronic pancreatitis (CP) may cause tumor-like lesions, creating a challenge in distinguishing between CP and pancreatic ductal adenocarcinoma (PDAC) in a patient. Given that invasive surgery is a standard cancer treatment, we aimed to examine whether a noninvasive diagnostic tool utilizing serum cytokines could safely differentiate between PDAC and CP.
Methods: A pre-operative serum panel comprising 48 inflammatory cytokines, CA19-9, and C-reactive protein (CRP) was analyzed, consisting of 231 patients, 186 with stage IeIII PDAC and 45 with CP. We excluded PDAC patients who underwent neoadjuvant therapy and those CP patients with other active malignancies. The laboratory variables most associated with PDAC diagnosis were assessed using logistic regression and selected using the lasso method.
Results: The cytokines CTACK, GRO-a, and b-NGF were selected alongside CA19-9 and CRP for our differential diagnostic model. The area under the curve (AUC) for our differential diagnostic model was 0.809 (95% confidence interval [CI] 0.738e0.880), compared with 0.791 (95% CI 0.728e0.854) for CA19-9 alone (not significant).
Conclusions: We found that inflammatory cytokines CTACK, GRO-a, and b-NGF alongside CA19-9 and CRP may help distinguish PDAC from CP.